Reassessment of views on public administration in the field of physical culture and sports in Ukraine under martial law (Law and Safety, 2024)
The scientific research is aimed at determining the forms of public administration in the field of physical culture and sports, in particular, at clarifying the peculiarities of this field in the conditions of martial law. In order to fulfill the tasks of the research, the author analyzed the forms and means of public administration in the field of physical culture and sports, determined the state of their legal regulation, taking into account the substantiated provisions regarding the need to increase the efficiency of the use of some of them in wartime conditions.According to the results of the conducted research, it has been established that public administration in the field of physical culture and sports is the activity of public administration subjects regulated by laws and other normative legal acts, aimed at the implementation of laws and other normative legal acts, including making administrative decisions, provision of administrative services established by legislation regarding the development of physical culture and sports.Forms of public administration in the field of physical culture and sports are systematized, in particular: issuance of normative acts of public administration in the field of physical culture and sports, their application and implementation of material and technical measures; provision of administrative services by carrying out registration, permit (licensing) and approval procedures in the field of physical culture and sports; conclusion of administrative contracts in the field of physical culture and sports regarding the delegation of management powers to local sports federations with the minimization of centralized management; implementation of public control over compliance with legislation in this area, detection, recording of violations and application of measures of legal responsibility.It has been established that in the conditions of martial law and post-war period, there will be following most effective forms of public administration in the field of physical culture and sports: attraction of investments in the reconstruction of destroyed or damaged infrastructure; further development and investment of veteran sports and sports aimed at restoring the physical and psychological shape of military personnel, involving the military in the sports movement and reviving the country on the international arena, as well as simplifying the system of providing administrative services in the specified areas.
Keywords: administrative and legal relations; public administration; public administration in the field of physical culture and sports; administrative services; administrative procedures; administrative responsibility.